2005
DOI: 10.1016/j.cell.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ Couples Hepatocyte Death to Cytokine-Driven Compensatory Proliferation that Promotes Chemical Hepatocarcinogenesis

Abstract: IkappaB kinase beta (IKKbeta), required for NF-kappaB activation, links chronic inflammation with carcinogenesis. We investigated whether IKKbeta is involved in chemically induced liver cancer, a model not involving overt inflammation. Surprisingly, mice lacking IKKbeta only in hepatocytes (Ikkbeta(Deltahep) mice) exhibited a marked increase in hepatocarcinogenesis caused by diethylnitrosamine (DEN). This correlated with enhanced reactive oxygen species (ROS) production, increased JNK activation, and hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
1,199
8
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,086 publications
(1,288 citation statements)
references
References 48 publications
59
1,199
8
13
Order By: Relevance
“…The TNAP-AID mouse model exhibits several characteristics of human HCC, in that the mice develop HCC spontaneously and the HCC tissue expresses a-fetoprotein and that it has the p53 gene mutations, some of which cause the same amino acid replacements as those seen in human tumours. Earlier HCC mouse models include mice with genetic modifications of Lkb1, Mdr2, Aox and Pten genes (Fan et al, 1998;Nakau et al, 2002;Horie et al, 2004;Katzenellenbogen et al, 2006), transgenic mice overexpressing c-myc, transforming growth factor-a, transforming growth factor-b1, HBx of hepatitis B virus and HCV core (Sandgren et al, 1989;Kim et al, 1991;Murakami et al, 1993;Koike et al, 1994Koike et al, , 2002Factor et al, 1997;Riehle et al, 2008) and chemical-or diet-induced HCC (Sell, 2001;Maeda et al, 2005;Ma et al, 2006;Sakurai et al, 2006). In contrast to these models, our TNAP-AID model is unique because it does not arbitrarily target specific oncogenes, tumour suppressors or stability genes.…”
Section: Discussionmentioning
confidence: 99%
“…The TNAP-AID mouse model exhibits several characteristics of human HCC, in that the mice develop HCC spontaneously and the HCC tissue expresses a-fetoprotein and that it has the p53 gene mutations, some of which cause the same amino acid replacements as those seen in human tumours. Earlier HCC mouse models include mice with genetic modifications of Lkb1, Mdr2, Aox and Pten genes (Fan et al, 1998;Nakau et al, 2002;Horie et al, 2004;Katzenellenbogen et al, 2006), transgenic mice overexpressing c-myc, transforming growth factor-a, transforming growth factor-b1, HBx of hepatitis B virus and HCV core (Sandgren et al, 1989;Kim et al, 1991;Murakami et al, 1993;Koike et al, 1994Koike et al, , 2002Factor et al, 1997;Riehle et al, 2008) and chemical-or diet-induced HCC (Sell, 2001;Maeda et al, 2005;Ma et al, 2006;Sakurai et al, 2006). In contrast to these models, our TNAP-AID model is unique because it does not arbitrarily target specific oncogenes, tumour suppressors or stability genes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, which utilized a mouse model of spontaneous hepatitis followed by hepatocellular carcinoma, inhibition of NF-kB in hepatocytes through regulatable IkBa super-repressor expression did not block hepatitis or the earliest stages of neoplasia; however, inhibition of NF-kB at later stages (either through IkBa expression or through TNF antibodies) induced apoptosis and blocked progression to hepatocellular carcinoma. In a related study, Maeda et al (2005) showed that, although loss of IKKb in hepatocytes actually promotes chemical-induced hepatocarcinogenesis through a compensatory mechanism downstream of JNK-mediated cell death, knockout of IKKb in hemopoietic-derived Kupffer cells suppressed hepatocarcinogenesis, indicating that NF-kB expression in these cells is crucial for the inflammation-mediated neoplastic growth.…”
Section: Roles For Nf-jb In Inflammation-associated Cancersmentioning
confidence: 99%
“…As discussed above, TNFα production by inflammatory cells is largely dependent on p38α in chronic inflammation, such as hepatitis. Interestingly, liver cells lacking the NFkB activator IKKβ show decreased activities of DUSPs, which leads to enhanced JNK1 phosphorylation and increased liver carcinogenesis (Maeda et al, 2005).…”
Section: Crosstalk Between Mapk Signaling In Inflammation and Cancermentioning
confidence: 99%